The crystal structure of 3,4-dichlorobenzoic acid chloride, C7H3Cl3O - Hosten Eric C.; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C7H3Cl3O, monoclinic, P21/c (no. 14), a = 12.0518(15) Å, b = 9.7403(11) Å, c = 6.9562(9) Å, β = 99.047(4)°, V = 806.42(17) Å3, Z = 4, Rgt(F) = 0.0316, wRref(F2) = 0.0793, T = 200 K.